Genomic restriction fragment analysis of fowlpox-virus vaccine strain and field isolates using EcoRI, Sal I and Pst I restriction endonucleases - MISHRA, S S; MALLICK, B B (The Indian Journal of Animal Sciences, 2013)
Fow-pox-virus [VR] vaccine strain and 2 field isolates were propagated in chicken-embryofibroblast-cell culture and purified by sucrose gradient ultracentrifugation. Transmission eleclronmicroscopy revealed the purified virus showing characteristic fowlpox-virus morphology with bilayer structure and surface tubular clements. The viral DNA was extracted and analysed after digestion with EcoRl, Sal I and Pst I restriction cndonucleases. BeoRI digestion produced 24 well resolved fragments with some comigrating_ fragments and analysis on a seperate gel revealed 40 restriction fragments. Sal I and Pst I digestion revealed a large unresolved fragments with 4 and 18 well resolved fragments respectively. The 3 viruses showed similar electrophoretic pattern of DNA restriction fragments indicating them to be genetically almost similar.